Diversity and ethnobotany of plants used as natural dye in traditional woven by local community in Belu District, Indonesia - WILHELMINA SERAN; LUDJI MICHAEL RIWU KAHO; MAMIE ELSYANA PELLONDO’U; ASTIN ELISE MAU; YUSRATUL AINI; NORMAN P. L. B. RIWU KAHO; MUHAMAD SOIMIN (Society for Indonesian Biodiversity, 2024)
Abstract. Seran W, Kaho LMR, Pellondo’u ME, Mau AE, Aini Y, Kaho NPLBR, Soimin M. 2024. Diversity and ethnobotany of plants used as natural dye in traditional woven by local community in Belu Regency, Indonesia. Biodiversitas 25: 4415-4424. Natural dye plants used by indigenous people for coloring woven fabrics are considered an important and unique Traditional Ecological Knowledge (TEK), especially in East Nusa Tenggara, Indonesia, which has high biodiversity and endemicity. This study is aimed to document the diversity, conservation status and ethnobotanical knowledge of dye-producing plant species used by local community in Belu District, East Nusa Tenggara Province. We used in-depth interviews with local weavers to collect data on plants used as natural dyes and observed the processes of extracting dyes and coloring the yarn. We documented 18 plant species used as dye for traditional tenun ikat (tied woven). The coloring process includes oiling the yarn, tying, measuring, dyeing, and drying, followed by weaving process. Stems and leaves are the most used part for producing dyes (each with 39%), followed by rhizomes (11%), fruits (6%) and roots (5%). Based on conservation status, only one species is conservation concern with status of endangered, i.e., Tectona grandis L.f., which produce purple and red colors. This study is useful as a record to preserve the rich ethnobotanical knowledge on the use of plants for coloring materials in the eastern region of Indonesia, and to raise awareness of the importance of documenting and conserving traditional plant-based practices.